(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper explores the role of e e-government initiatives in enhancing transparency and accountability within local governance. By examining various case studies and theoretical frameworks, the research highlights how digital platforms facilitate citizen engagement, streamline administrative processes, and promote openness in decision decision-making. The study employs a mixed mixed-methods approach, integrating qualitative and quantitative data to assess the impact of e e-government on public trust and governance effectiveness. Findings indicate that well well-implemented e e-government services significantly improve transparency, reduce corruption, and foster a more accountable local government. The pap er concludes with recommendations for optimizing e e-government strategies to further enhance local governance.